ST11 Carbapenem-Resistant Klebsiella pneumoniae Clone Harboring blaNDM Replaced a blaKPC Clone in a Tertiary Hospital in China - Qiaoyan Duan; Qi Wang; Shijun Sun; Qiaozhen Cui; Qi Ding; Ruobing Wang; Hui Wang (MDPI AG, 2022)
The nosocomial spread of carbapenem-resistant Enterobacterales (CRE) is extremely common, resulting in severe burdens on healthcare systems. In particular, the high-risk Klebsiella pneumoniae ST11 strain has a wide endemic area in China. The current study describes the results of continuous monitoring of CRE genotypes and phenotypes in a tertiary hospital in North China from 2012 to 2020. A total of 160 isolates were collected, including 109 Klebsiella. pneumoniae (68.13%), 29 Escherichia coli (26.60%), 12 Enterobacter cloacae (7.50%), and 10 other strains (6.25%). A total of 149 carbapenemase genes were detected, of which blaKPC-2 (51.0%) was the most common, followed by blaNDM-1 (22.82%), and blaNDM-5 (23.49%). Based on multi-locus sequence typing, the ST11 strain (66.1%) dominates K. pneumoniae, followed by ST15 (13.8%). Interestingly, the proportion of blaNDM (22.2%, 16/72) in ST11 K. pneumoniae was significantly increased in 2018-2019. Hence, whole-genome sequencing was performed on ST11 K. pneumoniae. Growth curves and in vitro competition experiments showed that K. pneumoniae carrying blaNDM exhibited a stronger growth rate (p < 0.001) and competition index (p < 0.001) than K. pneumoniae carrying blaKPC. Moreover, K. pneumoniae carrying blaNDM had a stronger biofilm-forming ability than K. pneumoniae carrying blaKPC (t = 6.578; p < 0.001). K. pneumoniae carrying blaKPC exhibited increased defense against bactericidal activity than K. pneumoniae carrying blaNDM. Thus, ST11 K. pneumoniae carrying blaNDM has strong adaptability and can locally replace K. pneumoniae carrying blaKPC to become an epidemic strain. Based on these findings, infection control and preventive measures should focus on the high-risk ST11-K. pneumoniae strain.